Are fearful boys at higher risk for anxiety? Person-centered profiles of toddler fearful behavior predict anxious behaviors at age 6 - Zhou, Anna M.; Trainer, Austen; Vallorani, Alicia; Fu, Xiaoxue; Buss, Kristin A. (Frontiers in Psychology, 2022)
Dysregulated fear (DF), the presence of fearful behaviors in both low-threat and high-threat contexts, is associated with child anxiety symptoms during early childhood (e.g., Buss et al., 2013). However, not all children with DF go on to develop an anxiety disorder (Buss & McDoniel, 2016). The present study leveraged data from two longitudinal cohorts (N = 261) to: (1) use person-centered methods to identify profiles of fearful temperament, (2) replicate findings linking DF to anxiety behaviors in kindergarten, (3) test if child sex moderates associations between DF and anxiety behaviors, and (4) examine the consistency of findings across multiple informants of child anxiety behaviors. We identified a normative fear profile (low fear in low-threat contexts, high fear in high-threat contexts), a low fear profile (low fear across both low- and high-threat contexts) and a DF profile (high fear across both low- and high-threat contexts). Results showed that probability of DF profile membership was significantly associated with child self-report of overanxiousness, but not with parent-report of overanxiousness. Associations between DF profile membership and overanxiousness was moderated by child sex such that these associations were significant for boys only. Additionally, results showed that probability of DF profile membership was associated with both parent-report of social withdrawal and observations of social reticence, but there were no significant associations with child self-report of social withdrawal. Results highlight the importance of considering person-centered profiles of fearful temperament across different emotion-eliciting contexts, and the importance of using multiple informants to understand associations with temperamental risk for child anxiety.